The effectiveness of complementary manual therapies for pregnancy-related back and pelvic pain: A systematic review with meta-analysis. Issue 38 (September 2016) - Hall, Helen; Cramer, Holger; Sundberg, Tobias; Ward, Lesley; Adams, Jon; Moore, Craig; Sibbritt, David; Lauche, Romy
Abstract: Background: Low back pain and pelvic girth pain are common in pregnancy and women commonly utilize complementary manual therapies such as massage, spinal manipulation, chiropractic, and osteopathy to manage their symptoms. Objective: The aim of this systematically review was to critically appraise and synthesize the best available evidence regarding the effectiveness of manual therapies for managing pregnancy-related low back and pelvic pain. Methods: Seven databases were searched from their inception until April 2015 for randomized controlled trials. Studies investigating the effectiveness of massage and chiropractic and osteopathic therapies were included. The study population was pregnant women of any age and at any time during the antenatal period. Study selection, data extraction, and assessment of risk of bias were conducted by 2 reviewers independently, using the Cochrane tool. Separate meta-analyses were conducted to compare manual therapies to different control interventions. Results: Out of 348 nonduplicate records, 11 articles reporting on 10 studies on a total of 1198 pregnant women were included in this meta-analysis. The therapeutic interventions predominantly involved massage and osteopathic manipulative therapy. Meta-analyses found positive effects for manual therapy on pain intensity when compared to usual care and relaxation but not when compared to sham interventions. Acceptability did not differ between manual therapy and usual care or sham interventions. Conclusions: There is currently limited evidence to support the use of complementary manual therapies as an option for managing low back and pelvic pain during pregnancy. Considering the lack of effect compared to sham interventions, further high-quality research is needed to determine causal effects, the influence of the therapist on the perceived effectiveness of treatments, and adequate dose–response of complementary manual therapies on low back and pelvic pain outcomes during pregnancy.